Isolation and characterization of cellulase producing bacteria / Muhammad Alif Fitri Zainor - Zainor, Muhammad Alif Fitri (Faculty of Plantation and Agrotechnology, 2018)
The microbial succession occurs because each establishment of a new species modifies the environment. Decomposing leaves and other organic matter produces rich top soil. Since plant are made up from cellulose, this experiment purposely to isolate and identify bacteria that able to decompose cellulose. There are a research that studied about the cellulose that help in decomposition. But it is more on using the fungus in decomposition which is some of them are using the Tricodermastrains. This fungus are believed to help in speeding up the time of decomposition of empty fruit bunch in oil palm plantation and improves the fertility of soil through the releasing of nutrient to the soil. The application of bacteria in producing cellulase is not widely used. If compared the bacteria and the fungi, the growth rate of the bacteria is higher and it has a good potential to be used in production of cellulase. So, in this study it is really important to identify the most efficient cellulase producing bacteria. From the end result, the selected bacteria which is from the Bacillus methanolicusincorporated to the efb compost shown the increased in the nutrient content which the bacteria positively reacted to the efb.